One-pot high yield synthesis of Ag nanoparticle-embedded biochar hybrid materials from waste biomass for catalytic Cr(vi) reduction. Issue 4 (14th July 2016) - Liu, Wu-Jun; Ling, LiLi; Wang, Yuan-Ying; He, Hui; He, Yan-Rong; Yu, Han-Qing; Jiang, Hong
Abstract : The Ag nanoparticle-embedded biochar hybrid material (Ag@biochar) was synthesized in one-pot by fast pyrolysis of the Ag preloaded biomass, and its catalytic effect on HCOOH-induced Cr(vi ) reduction was evaluated. Abstract : Disposal of heavy metal-contaminated biomass obtained from phytoremediation or biosorption by using environmentally benign methods is a big challenge. In this study, we proposed a win–win strategy to recycle Ag-contaminated biomass by fast pyrolysis to obtain renewable bio-oil and achieve the catalytic reduction of Cr(vi ) with the Ag-embedded biochar. We herein focused on the one-pot synthesis of a Ag nanoparticle-embedded biochar hybrid material (Ag@biochar) by fast pyrolysis of the Ag preloaded biomass and its catalytic effect on Cr(vi ) reduction. The results show that Ag@biochar can completely catalytically reduce Cr(vi ) in aqueous solution within 20 min using formic acid as a reducing agent at 323 K. The particle size of Ag NPs on the biochar was found to be pyrolysis temperature dependent and played an important role in the reduction of Cr(vi ). We found that the reduction of Cr(vi ) catalyzed by Ag@biochar follows a CO (produced from HCOOH decomposition) reduction mechanism which is quite different from the H2 reduction mechanism with catalysis of some noble metal based catalysts ( e.g. Pd and Pt). This study offers a sustainable approach for simultaneous disposal of the biomass waste and synthesis of functional materials and might be expanded in the recycling of other metal-contaminated biomass ( e.g. Cu, Ni, Co, Zn, and Fe).